Emotional labor and its association with emotional exhaustion through cultural intelligence. Issue 4 (1st October 2020) - Rafiq, Nazia; Abbasi, Abdus Sattar; Ali Sair, Shrafat; Mohiuddin, Muhammad; Munir, Ismat
Abstract: This study seeks to investigate the association of emotional labour with emotional exhaustion among employees. This study focuses on the moderating role of cultural intelligence between emotional labour and emotional exhaustion. The proposed model has been tested through quantitative method approach in light of Conservation of Resources Theory (COR). The data collected from 520 employees from hotel sector under multistage sampling technique has been analysed. The gathered data will be examined through statistical techniques, are estimated to prove the proposed relationships. The study will be beneficial for industry practitioners, managers and leaders who can take advantage from the study and make strategies to minimise the negative effects of emotional labour in their respective organisations.